2014
DOI: 10.1163/22134913-00002011
|View full text |Cite
|
Sign up to set email alerts
|

Event Segmentation and Biological Motion Perception in Watching Dance

Abstract: We used a combination of behavioral, computational vision and fMRI methods to examine human brain activity while viewing a 386 s video of a solo Bharatanatyam dance. A computational analysis provided us with a Motion Index (MI) quantifying the silhouette motion of the dancer throughout the dance. A behavioral analysis using 30 naïve observers provided us with the time points where observers were most likely to report event boundaries where one movement segment ended and another began. These behavioral and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Here also, from the constituent RDM's, it can be seen that some of the stimuli that stand out for cLightness are also rated very dissimilar to other stimuli on bMotion. Indeed, the region (EBA, or including EBA) in the OTC where cLightness, bMotion, and cSymmetry (left only) overlap has previously been found in a study where computational parameters as well as behavioral parameters of a dance video covary with the BOLD signal (Noble et al 2014).…”
Section: Relations Between Stimulus Categories Computational and Behmentioning
confidence: 71%
See 1 more Smart Citation
“…Here also, from the constituent RDM's, it can be seen that some of the stimuli that stand out for cLightness are also rated very dissimilar to other stimuli on bMotion. Indeed, the region (EBA, or including EBA) in the OTC where cLightness, bMotion, and cSymmetry (left only) overlap has previously been found in a study where computational parameters as well as behavioral parameters of a dance video covary with the BOLD signal (Noble et al 2014).…”
Section: Relations Between Stimulus Categories Computational and Behmentioning
confidence: 71%
“…The former only activated left dorsal premotor, dorsolateral prefrontal cortex, and medial frontal cortex. Another recent study that gets closer to understanding movement features and brain activity calculated the relation between the motion index (an index of whole-body movement) and brain activation (Noble et al 2014). Results showed that the motion index was related to brain activity in a single cluster in the right inferior temporal gyrus, an area frequently reported in the studies of body movement perception as seen in a recent meta-analysis (Grosbras et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Visual familiarity was induced in the current study by repeated presentation of the same stimulus dance phrase. This approach clearly differs from the approaches taken in other segmentation studies in which observes typically watched the same action twice, in part with different instructions (e.g., coarse vs. fine segmentation, Zacks et al, 2009 ; Sargent et al, 2013 ; or just watching vs. segmenting, Noble et al, 2014 ). Under natural conditions, actions are not repeated in exactly the same way, and segmentation occurs spontaneously as part of perceptual processing.…”
Section: Experiments 2: Segmentation Of a Dance Phrase Before And Aftementioning
confidence: 83%
“…Dance expertise should therefore not only enable dancers to perform movement phrases fluently, but should also influence their perception of observed movement material in favor of fluency and greater over-all connectedness. Only few studies have investigated the segmentation of dance-like actions (e.g., Pollick et al, 2012 ; Noble et al, 2014 ), and so far none has focused on effects of dance expertise on segmentation. Evidence from preliminary studies suggests that observers' dance expertise affects the segmentation of dance-like actions, but not of other actions that have an obvious external goal (Bläsing et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yet dance is a fluent combination of movements extending over time and potentially coded as a specifically choreographed chain of actions. More recent research on dance has started to make use of longer and more naturalistic stimuli (Jola et al 2012;Jola & Grosbras 2014;Noble et al 2014;Grosbras et al 2012b, Herbec et al in press) however the question of how single movements or gestures are combined into a coherent whole has been largely left unstudied.…”
Section: Introductionmentioning
confidence: 99%